ANALISIS PROSEDUR REKRUTMEN DALAM UPAYA PEMENUHAN TENAGA KERJA - Farika Nikmah; Halid Hasan; Lilies Nur Ainie (Politeknik Negeri Malang, 2018)
Human Resources (HR) is an important component in the company for help in carrying out operational functions. To obtain qualified employees and have high competence, then in the initial stages, of a company should make the process of recruitment. The aim of this study is to determine the recruitment procedures by analyzing existing data in recruitment procedures and make comparisons with the theory so that it can determine the correct recruitment procedures.